2019
DOI: 10.1634/theoncologist.2018-0561
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Split Schedule Versus Conventional Schedule Neoadjuvant Cisplatin-Based Chemotherapy for Muscle-Invasive Bladder Cancer

Abstract: Neoadjuvant cisplatin‐based chemotherapy (NAC; 70 mg/m2) is standard of care for muscle‐invasive bladder carcinoma (MIBC). Many patients (pts) cannot receive cisplatin because of renal impairment, and administration of cisplatin 35 mg/m2 on day 1 + 8 or 1 + 2 (i.e., split schedule) is a commonly used alternative. In this retrospective analysis, we compared complete (pT0) and partial ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The decision to give dose-dense Methotrexate, Vinblastine, Adriamycin and Cisplatin (ddMVAC) every two weeks or Gemcitabine and Cisplatin (Gem/Cis) every three weeks as cisplatin-based NAC is determined by the medical oncologist according to local hospital protocols. Patients with a Creatinine Clearance (CrCl) between 40 and 60 ml/min are eligible for split-dose cisplatin and gemcitabine [20].…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision to give dose-dense Methotrexate, Vinblastine, Adriamycin and Cisplatin (ddMVAC) every two weeks or Gemcitabine and Cisplatin (Gem/Cis) every three weeks as cisplatin-based NAC is determined by the medical oncologist according to local hospital protocols. Patients with a Creatinine Clearance (CrCl) between 40 and 60 ml/min are eligible for split-dose cisplatin and gemcitabine [20].…”
Section: Study Populationmentioning
confidence: 99%
“…A further exclusion criterion is the presence of CIS in the prostatic urethra at diagnostic TUR, since the prostatic urethra is a difficult site for re-staging TUR biopsies, especially within a close surveillance protocol. Split-dose cisplatinbased NAC regimens for patients with impaired renal function are allowed within the PRE-PREVENCYS trial as these regimens have been shown non-inferior to conventional regimens in terms of pathological downstaging [20]. Therefore, patients with a CrCl between 40 and 60 ml/min are thus candidates for this split-dose regimen and will be included in this study.…”
Section: Exclusionmentioning
confidence: 99%
“…Timed urine collections, although preferable, are infrequently utilized due to inconvenience and cost. In patients with impaired renal function (renal clearance ≥50 mL/min), split dose GC (cisplatin 35 mg/m 2 on day 1 and day 8) [81,91,[162][163][164][165] and dose reduction (25-50%) of standard GC (cisplatin 70 mg/m 2 every 3 weeks) are options, although data supporting these approaches remains limited [166][167][168]. For patients with baseline renal function <50 ml/min, generally the use of cisplatin-based NAC is not supported by adequate safety data.…”
Section: Cisplatin-ineligible Patientsmentioning
confidence: 99%
“…In the current issue of The Oncologist , Osterman et al report results of a retrospective multi‐institutional 1:1 matched cohort study of 80 patients with MIBC who received either split‐dose or conventional‐dose CBNCC. In comparison with conventional dose, patients receiving split dose were older (71 vs. 65.5 years, p = .007) and had lower median glomerular filtration rate (63.5 vs. 74.7 mL/min, p = .003).…”
Section: Examples Of Neoadjuvant Immunotherapy Trials In Muscle‐invasmentioning
confidence: 99%
“…Moreover, The Cancer Genome Atlas has reported potential therapeutic targets in 69% of the analyzed tumors, which provides the setting for evaluation of new therapeutic approaches [17]. At present, more than 50 neoadjuvant trials are ongoing in MIBC [18]. These trials include PD-1/PD-L1 therapies either as a single agent or in combination with CTLA-4 antibodies, other checkpoint inhibitors, chemotherapy, PARP inhibitors, or other agents.…”
mentioning
confidence: 99%